2015
DOI: 10.1002/ca.22515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical considerations of the glandular branch of the lacrimal artery

Abstract: The lacrimal artery is classically described as a branch of the ophthalmic artery supplied by the internal carotid. In this study, 25 orbits were dissected to identify variations in glandular branching and to compare them to previously published accounts. The glandular branching patterns of the lacrimal artery fall into two categories, those that branch (56%) and those that do not branch (44%). We found the medial and lateral glandular branches to be equal in diameter with a divergence of 2.67-40.58 mm proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Morphometry of the Lacrimal Artery: The LA originates at the apex of the orbit and follows the lacrimal nerve anteriorly above the superior margin of the lateral rectus muscle to supply the lacrimal gland. 18 We measured LA diameter 0.35 ± 0.12 mm and the LA was the largest branch of the OA. However, the mean diameter was measured 0.70 mm by Lang and Kageyama 7 and 0.50 mm by Perrini et al 8 Our result was lower than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Morphometry of the Lacrimal Artery: The LA originates at the apex of the orbit and follows the lacrimal nerve anteriorly above the superior margin of the lateral rectus muscle to supply the lacrimal gland. 18 We measured LA diameter 0.35 ± 0.12 mm and the LA was the largest branch of the OA. However, the mean diameter was measured 0.70 mm by Lang and Kageyama 7 and 0.50 mm by Perrini et al 8 Our result was lower than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,17 Perrini et al 8 found that the LA originated from the MMA at a rate of 29%. Kluckman et al 18 performed dissections on 25 orbits and they showed 23 lacrimal glands were supplied by the OA system, one was supplied by an anastomotic branch with MMA and the other one was supplied both the anterior deep temporal artery and the OA. In present study, we found that all LAs arose from the OA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five cadaver heads from the university hospital’s body donation program for medical education and scientific research were used to develop this surgical technique (Table 1 ). Three heads were preserved using the modified Thiel-soft-embalming protocol [ 5 , 6 ]. This fixation procedure provides realistic visual and haptic properties without the risk of infection or time pressure due to tissue degradation.…”
Section: Methodsmentioning
confidence: 99%